Reconfirmation of Skempton-Bjerrum 2D to 3D settlement conversion using FEM of full scale embankments - S. Chaiyaput; D.T. Bergado (Lowland Technology International, 2018)
The soil is a production of natural process, which is highly variable with very complex properties, and soil behavior can be difficult to calculate. Numerical Simulation can be applied to deal with the numerous aspects of complex geotechnical structures. The 3D FEM simulation model can present the conditions of the geotechnical project in details and assumptions, which are similar to actual situations, but the process of running the 3D FEM analysis takes longer computer time. Therefore, 2D FEM simulation model is proposed to reduce calculation time, but the prediction results are usually overestimated. Accordingly, this paper re-analyzed the 2D analysis to represent the performance of 3D analysis based on Skempton-Bjerrum method. The simulated 2D and 3D FEM settlement results had been carried out and compared with the measured data of two full scale embankments including the dissipation of the excess pore pressure. Consequently, it was confirmed that predicted result of 2D and 3D FEM numerical simulation agreed with the correction of Skempton-Bjerrum method that can be applied to predict the final settlements in 3D conditions.